Komunikasi dalam Pemberdayaan Kelompok Difabel (Studi pada UMKM Batik Wistara Indonesia) - Siti Khalimatus Sya’diyah (Jurnal Ilmu Komunikasi, 2020)
This article discusses how to communicate in empowering groups with disabilities at UMKM Batik Wistara Indonesia. The purpose of this study is to describe the communication process carried out by UMKM Batik Wistara Indonesia to these disabled employees. This research uses a qualitative approach with descriptive methods. The results of this study indicate that the communication process carried out by employees with disabilities uses the Schramm model and the interactional communication model, by applying a circular communication pattern. The form of the communication process carried out is interpersonal communication by referring to no limitations in communicating. Owners and managers of UMKM Batik Wistara Indonesia, when communicating with disabled employees at UMKM use egalitarian ways, so that employees can work comfortably without pressure from the manager